Oxalate-metabolising genes of the white-rot fungus Dichomitus squalens are differentially induced on wood and at high proton concentration. - Miia R Mäkelä (Public Library of Science (PLoS), 2014)
Oxalic acid is a prevalent fungal metabolite with versatile roles in growth and nutrition, including degradation of plant biomass. However, the toxicity of oxalic acid makes regulation of its intra- and extracellular concentration crucial. To increase the knowledge of fungal oxalate metabolism, a transcriptional level study on oxalate-catabolising genes was performed with an effective lignin-degrading white-rot fungus Dichomitus squalens, which has demonstrated particular abilities in production and degradation of oxalic acid. The expression of oxalic-acid decomposing oxalate decarboxylase (ODC) and formic-acid decomposing formate dehydrogenase (FDH) encoding genes was followed during the growth of D. squalens on its natural spruce wood substrate. The effect of high proton concentration on the regulation of the oxalate-catabolising genes was determined after addition of organic acid (oxalic acid) and inorganic acid (hydrochloric acid) to the liquid cultures of D. squalens. In order to evaluate the co-expression of oxalate-catabolising and manganese peroxidase (MnP) encoding genes, the expression of one MnP encoding gene, mnp1, of D. squalens was also surveyed in the solid state and liquid cultures. Sequential action of ODC and FDH encoding genes was detected in the studied cultivations. The odc1, fdh2 and fdh3 genes of D. squalens showed constitutive expression, whereas ODC2 and FHD1 most likely are the main responsible enzymes for detoxification of high concentrations of oxalic and formic acids. The results also confirmed the central role of ODC1 when D. squalens grows on coniferous wood. Phylogenetic analysis revealed that fungal ODCs have evolved from at least two gene copies whereas FDHs have a single ancestral gene. As a conclusion, the multiplicity of oxalate-catabolising genes and their differential regulation on wood and in acid-amended cultures of D. squalens point to divergent physiological roles for the corresponding enzymes.